Pr3+ doped NaYF4 and LiYF4 nanocrystals combining visible-to-UVC upconversion and NIR-to-NIR-II downconversion luminescence emissions for biomedical applications. Issue 39 (30th September 2022) - Tsang, Min Ying; Fałat, Patryk; Antoniak, Magda A.; Ziniuk, Roman; Zelewski, Szymon J.; Samoć, Marek; Nyk, Marcin; Qu, Junle; Ohulchanskyy, Tymish Y.; Wawrzyńczyk, Dominika
Abstract : NaYF4 and LiYF4 nanoparticles co-doped with Pr 3+ and Yb 3+ are reported, manifesting 980 nm excited downconversion luminescence peaked at 1320 nm for NIR-II bioimaging and 447 nm excited upconversion luminescence at 275 nm for germicide action. Abstract : Lanthanide-doped fluoride nanocrystals (NCs) are known to exhibit unique optical properties, such as upconversion and downconversion luminescence (UCL and DCL), which can be employed for various applications. In this work, we demonstrate that by doping praseodymium(iii ) and ytterbium(iii ) ions (Pr 3+ and Yb 3+ ) into a nanosized fluoride matrix ( i.e. NaYF4 and LiYF4 ), it is possible to combine their UCL and DCL properties that can be concurrently used for biomedical applications. In particular, the emissive modes combined in a single nanoparticle co-doped with Pr 3+ and Yb 3+ include DCL emission (excited at 980 nm and peaked at 1320 nm), which can be used for near infrared (NIR) DCL bioimaging in the NIR-II window of biological tissue transparency (∼1000–1350 nm) and UCL emission (excited at 447 nm and peaked at 275 nm) that can be employed for germicide action ( via irradiation by light in the UVC range). A possibility of the latter was demonstrated by the denaturation of double-stranded DNA (dsDNA) into single-stranded ones that was caused by the UVC UCL emission from the NCs under 447 nm irradiation; it was evidenced by the hyperchromicity observed in the irradiated dsDNA solution and also by a fluorometric analysis of DNA unwinding (FADU) assay. Concurrently, the possibility of NIR-II luminescence bioimaging through biological tissues (bovine tooth and chicken flesh) was demonstrated. The proposed concept paves a way for NIR-II imaging guided antimicrobial phototherapy using lanthanide-doped fluoride nanocrystals.